Unbegleitete minderjährige Geflüchtete Ihre Lebenssituationen und Perspektiven in Deutschland - Thomas, Stefan (Kultur und soziale Praxis, 2018)
This volume analyses life situations and perspectives of unaccompanied minor refugees in Germany from subjective, institutional and structural perspectives.